(untitled) (Research, Society and Development, 2024)
The Covid-19 pandemic event caused psychological changes in university students. The aim of this research was to perform an analysis of the mental condition of engineering students of a federal public university during the Covid-19 pandemic, seeking to understand the stressors that impact on the students’ lives. The sample consisted of 100 students, regularly enrolled, who signed the Free and Informed Consent Form (TCLE) and answered a sociodemographic and mental and emotional questionnaire and the Self Report Questionnare (SQR-20). The results obtained showed that 87% of the sample presented some type of minor psychic disorder. The comparations in the mental and emotional condition scales showed that the pandemic and the continuity of teaching were relevant factors for changes in stress and anxiety levels, which were already at levels that showed changes in the mental and emotional conditions of volunteers. Negative psychological effects, physical and mental fatigue for students’ health were evidenced, associated with an accumulation of workload and the presence of suicidal ideation in 13% of the sample. Therefore, factors resulting from the adoption of remote education as well as accumulation of half-yearly workload, added to the conditions resulting from the Covid-19 pandemic, have made structural weaknesses and deficiencies surface.